Tractate Yebamot - Guggenheimer, Heinrich W. (Studia Judaica, 2004)
This, the first volume of a five-volume edition of the third order of the Jerusalem Talmud, deals with Jewish marital law and related topics. The volume is concerned with levirate marriage, considering other Jewish sects at the same time, with forbidden marriages and the judicial treatment of missing husbands, with the incapability to marry, and with the status of married juveniles.